Simultaneous Determination of 23 Trans Fatty Acids in Common Edible Oils by Gas Chromatography-Mass Spectrometry - Yanping Cao; Xia Li; Kun Wang; Xianpeng Wu; Jie Zhang; Fengen Wang (Separations)
Trans fatty acids (TFAs) pose significant health risks, including cardiovascular disease and metabolic disorders. However, the lack of high-resolution, high-sensitivity, and high-throughput quantitative methods for TFA analysis has led to fragmented data on TFA content in edible oils, which constrains research on the quality assessment of edible oils. In this study, we developed a high-resolution and high-sensitivity gas chromatography-mass spectrometry method to simultaneously determine 23 TFA isomers. The method validation demonstrated good sensitivity, linearity, accuracy, and precision. Based on the proposed method, we analyzed 170 samples of 11 common edible oils, establishing a comprehensive TFA profile for each type. Ruminant fats (beef tallow, mutton tallow, butter) had high TFA levels (0.8–4.8 g/100 g), dominated by vaccenic acid (C18:1 t11) and conjugated linoleic acid, while vegetable oils (soybean, corn, peanut and sesame oil) exhibited lower concentrations (0.5–2.2 g/100 g), especially monounsaturated TFAs. Particularly, soybean oil was rich in C18:3 isomers, while shortening presented the closest similarity to sesame oil. Cluster analysis distinguished oils by TFA composition, highlighting low-TFA clusters (sunflower oil, pork lard, cream). In conclusion, the high-resolution, high-sensitivity, and high-throughput TFA quantification method developed in this study provides technical support for establishing characteristic TFA profiles in edible oils, while offering data support to further quality assessment.